2001
DOI: 10.1523/jneurosci.21-09-03104.2001
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 Prevents Glutamate-Mediated Cerebellar Granule Cell Death by Blocking Caspase-3-Like Activity

Abstract: Interleukin-10 (IL-10) has been shown to reduce neuronal degeneration after CNS injury. However, the molecular mechanisms underlying the neuroprotective properties of this cytokine are still under investigation. Glutamate exacerbates secondary injury caused by trauma. Thus, we examined whether IL-10 prevents glutamate-mediated cell death. We used rat cerebellar granule cells in culture because these neurons undergo apoptosis upon exposure to toxic concentrations of glutamate (100-500 microm) or NMDA (300 micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
145
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 177 publications
(151 citation statements)
references
References 58 publications
(86 reference statements)
4
145
1
1
Order By: Relevance
“…Once activated, caspases are responsible for the proteolytic cleavage of several substrates leading to cell death. Accordingly, it has been reported that there is an increase in both caspase-3 expression and activity when cultured neurons are treated with glutamate or NMDA (33,34,(61)(62)(63). We assessed the caspase-3 activity in cultured cortical neurons after glutamate treatment and found that the caspase-3 activity was significantly reduced in the cortical neurons of AC1 KO mice, but not in the cortical neurons from AC8 KO mice, compared with wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once activated, caspases are responsible for the proteolytic cleavage of several substrates leading to cell death. Accordingly, it has been reported that there is an increase in both caspase-3 expression and activity when cultured neurons are treated with glutamate or NMDA (33,34,(61)(62)(63). We assessed the caspase-3 activity in cultured cortical neurons after glutamate treatment and found that the caspase-3 activity was significantly reduced in the cortical neurons of AC1 KO mice, but not in the cortical neurons from AC8 KO mice, compared with wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of caspase-3 is a hallmark of apoptotic cell death and precedes changes in nuclear morphology (33,34). To further confirm that glutamate could induce apoptotic neuronal death in our model system, we measured caspase-3 activity at various time points in extracts from cortical neuron cultures during the 8 h after treatment with 250 M glutamate.…”
Section: Genetic Deletion Of Ac1 Protects Against Neuronal Deathmentioning
confidence: 98%
“…Gangliosides increase neurotrophin release in cerebellar granule cells Cerebellar granule cells were prepared as previously described (31,32). At day 8 in vitro, cells were exposed for 5 or 15 min to either control medium alone or containing LIGA20 (5 M) or GM1 (30 M).…”
Section: Table IImentioning
confidence: 99%
“…Cerebellar granule cells were prepared from postnatal day 8 Sprague-Dawley rat pups (Taconic Farms Inc., Germantown, NY) as previously described (31,32). In brief, neurons were plated onto 1% poly-Llysine-precoated 100-mm plastic dishes at a density of 2.5 ϫ 10 6 cells/ml and grown in basal Eagle's medium (Invitrogen) containing glutamine (2 mM), fetal calf serum (10%), KCl (25 mM), gentamycin (100 g/ml), and penicillin/streptomycin (10,000 units/ml).…”
mentioning
confidence: 99%
See 1 more Smart Citation